2021
DOI: 10.1111/aos.15066
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of retinal oximetry in retinal vein occlusion: a review

Abstract: To review retinal vein occlusion (RVO) and its relationship with retinal oxygen saturation via automated retinal oximetry in eyes with RVO. Methods.A literature review was performed in PubMed and Medline until October 2021 utilizing specific keywords and cross-matched reference lists. Results.This review found RVO to be associated with risk factors including age, hypertension, cardiovascular and metabolic conditions, male gender, and glaucoma. These may be attributed to a breakdown of regulatory processes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…This is an indication of a clear correlation between metabolic and structural changes induced by inflammation. Our findings suggest that the retina is more hypoxic in the late presentation group and in the eyes that subsequently developed SGF (Belamkar et al., 2022; Eliasdottir et al., 2015; Jeppesen & Bek, 2017; Krejberg Jeppesen et al., 2021; Sinova et al., 2018; Stefansson et al., 2019) to result in increased extraction of oxygen as a consequence of prolonged inflammation‐related blood flow impairment in the acute uveitic phase of VKH disease. We hypothesise that inflammation‐induced blood flow impairment and exudative retinal detachment result in a retinal hypoxic condition, particularly in the late presentation group and among eyes that subsequently developed SGF.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This is an indication of a clear correlation between metabolic and structural changes induced by inflammation. Our findings suggest that the retina is more hypoxic in the late presentation group and in the eyes that subsequently developed SGF (Belamkar et al., 2022; Eliasdottir et al., 2015; Jeppesen & Bek, 2017; Krejberg Jeppesen et al., 2021; Sinova et al., 2018; Stefansson et al., 2019) to result in increased extraction of oxygen as a consequence of prolonged inflammation‐related blood flow impairment in the acute uveitic phase of VKH disease. We hypothesise that inflammation‐induced blood flow impairment and exudative retinal detachment result in a retinal hypoxic condition, particularly in the late presentation group and among eyes that subsequently developed SGF.…”
Section: Discussionmentioning
confidence: 74%
“…A consequent decrease in blood flow to the retina can lead to hypoxia. These studies reported lower oxygen saturation in retinal venules and a higher arteriovenous saturation difference in eyes with central retinal vein occlusion compared to their fellow eyes (Belamkar et al., 2022; Eliasdottir et al., 2015; Jeppesen & Bek, 2017; Krejberg Jeppesen et al., 2021; Sinova et al., 2018; Stefansson et al., 2019). In patients with central retinal vein occlusion, a significant negative correlation was found between the ischaemic index and vein saturation and a significant positive correlation between the ischaemic index and the arteriovenous saturation difference (Sinova et al., 2018).…”
Section: Discussionmentioning
confidence: 98%
“…As the shared pathogenesis of proliferative diabetic retinopathy (PDR), retinopathy of prematurity (ROP), and other retinal vasculopathies, ischemiainduced pathological retinal neovascularization is a common cause of irreversible blindness globally in various age groups [1][2][3]. Therefore, effective intervention has become crucial to reducing the severe vision loss caused by retinal neovascularization.…”
Section: Introductionmentioning
confidence: 99%